James Barry: between scalpels and secrets, a life that defied the norms - Gutiérrez, Jefferson J.; Castro, Joseph J.; Franco, Vicente A.; Panta, Irene N.; Quiroz, Arnaldo E. (Revista Gregoriana de Ciencias de la Salud, 2025)
James Barry, born like Margaret Ann Bulkley, faced rigid 19th-century rules after adopting a male identity to access medicine, a field forbidden to women. Her career included notable achievements such as the first documented Caesarean section in the British Empire with the survival of both mother and child, and reforms in military hospitals that improved sanitary conditions. Barry also promoted vaccination campaigns for marginalized groups, such as prisoners and lepers, revolutionizing public health. She performed as a good character and her obsession with hygiene and surgical innovation made her an influential figure. Her relationship with Lord Charles Somerset protected her secret, but generated controversies that marked her career. After her death, the discovery of her biological sex unleashed a scandal that did not overshadow her history in medicine.